KEPEMIMPINAN TRANSFORMASIONAL KEPALA SEKOLAH TERHADAP KUALITAS LAYANAN AKADEMIK - Lestari, Hana; Rahmawati, Ima; Ulfatul Hasanah, Siti (Evaluasi: Jurnal Manajemen Pendidikan Islam, 2024)
The quality of school academic services is an effort provided by educational institutions in the form of responsive, friendly and accurate service, providing individual attention, providing adequate facilities and administration to meet the expectations and satisfaction of users of educational services in the field of learning. The aim of this research is to describe the influence of transformational leadership on the quality of academic services at A-accredited private MTs in Pamijahan Bogor District. The number of samples taken was 102 teachers, using a probability sampling method with a simple random sampling technique. The research method used is quantitative research with data collection techniques using questionnaires. The data analysis technique used is simple linear regression. Based on the results of the analysis, it was found that transformational leadership has a positive effect on the quality of academic services. This shows that the stronger the transformational leadership, the higher the quality of academic services available at the school. Therefore, to improve the quality of academic services, we hope to pay more attention to the transformational leadership of school principals in order to improve the quality of academic services.